2022
DOI: 10.3390/medicina58030373
|View full text |Cite
|
Sign up to set email alerts
|

Inflammaging and Vascular Function in Metabolic Syndrome: The Role of Hyperuricemia

Abstract: Background and Objectives: Early vascular aging determines a more rapid course of age-related arterial changes. It may be induced by a proinflammatory state, caused by hyperuricemia and metabolic syndrome and their interrelationship. However, the impact of serum uric acid (SUA) on early arterial stiffening and vascular function remains uncertain. Materials and Methods: A total of 696 participants (439 women aged 50–65 and 257 men aged 40–55) from the Lithuanian High Cardiovascular Risk (LitHiR) primary prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…On the other hand, inflammasome-independent inflammatory mechanisms are neutrophils dependent to cause the production of cytokines. Soluble urate inflammatory pathways work in the intracellular environment, where the soluble UA has numerous inflammatory and oxidative actions like intracellular immunometabolic responses, inflammatory responses, free radicals damage, and cell self-consumption [35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, inflammasome-independent inflammatory mechanisms are neutrophils dependent to cause the production of cytokines. Soluble urate inflammatory pathways work in the intracellular environment, where the soluble UA has numerous inflammatory and oxidative actions like intracellular immunometabolic responses, inflammatory responses, free radicals damage, and cell self-consumption [35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, C-reactive protein and other cardiovascular damage markers that result from ROS are often elevated compared to normal weight individuals [37]. Furthermore, higher levels of circulating blood lipids and uric acid (hyperuricemia) in the obese, regardless of metabolic status, facilitate damage to both lipids (e.g., nitrosylated lipoproteins) and vascular endothelium [38]. However, in the short-term, MHO carries comparatively lower risks of ROS generation and these patients can more easily undergo exercise and diet interventions to further reduce oxidative stress generated by obesity.…”
Section: Damage From Reactive Oxygen Speciesmentioning
confidence: 99%
“…Hyperuricemia (HUA) is resulted from reduced uric acid excretion or abnormal purine metabolism and is inextricably linked to chronic kidney disease 1 , metabolic syndrome 2 , and type 2 diabetes 3 . A study found that HUA prevalence is 13.5% (17.3% in men, 10.0% in women) when age and sex are standardized 3 .…”
Section: Introductionmentioning
confidence: 99%